2012
DOI: 10.1590/s1677-04202012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n-propyl gallate on photosynthesis and physiological parameters in Dunaliella salina are affected by stressful conditions

Abstract: We studied the effects of n-propyl gallate, which is a plastid terminal oxidase inhibitor involved in chlororespiration, on photosynthesis and physiological parameters in Dunaliella salina grown under different salinities and under low or high irradiance using chlorophyll a fluorescence transient measurements and pigment analysis. The inhibitor up to 1 mM had an additive significant effect on the photosynthetic efficiency in the cell suspensions grown under low salinity and irradiance. However, in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…Thus, it is probably that the leaf extracts-induced β-carotene concentration increase could be brought about maintenance of Chl, in addition to its biosynthesis stimulation under leaf extracts-induced stress. It is in agreement with our previous results on propyl gallateinduced β-carotene under salt stress (Einali & Shariati 2012;Einali & Valizadeh 2015). Based on the results, the highest concentrations of both Chl and β-carotene were observed in cells exposed to 1 % eucalyptus and 2 % elderberry (Figs.…”
Section: Effects Of Leaf Extracts On Chlorophylls and β-Carotenesupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, it is probably that the leaf extracts-induced β-carotene concentration increase could be brought about maintenance of Chl, in addition to its biosynthesis stimulation under leaf extracts-induced stress. It is in agreement with our previous results on propyl gallateinduced β-carotene under salt stress (Einali & Shariati 2012;Einali & Valizadeh 2015). Based on the results, the highest concentrations of both Chl and β-carotene were observed in cells exposed to 1 % eucalyptus and 2 % elderberry (Figs.…”
Section: Effects Of Leaf Extracts On Chlorophylls and β-Carotenesupporting
confidence: 93%
“…It is known that Dunaliella accumulate large amount of β-carotene while cell division is retard. Thus, adverse environmental conditions, such as high salinity, low temperature, high irradiance, or nutrient deficiency increase the accumulation of β-carotene in this alga (BenAmotz et al 1982;Ben-Amotz & Avron 1983;Ben-Amotz 1996;Einali & Shariati 2012;Einali & Valizadeh 2015). Due to that, Dunaliella has been widely considered as an interesting model for studying β-carotene biosynthesis.…”
Section: Effects Of Leaf Extracts On Chlorophylls and β-Carotenementioning
confidence: 99%
“…Kalaji et al 2011, Bacarin et al 2011, however only limited number of studies used PI abs as indicator in stress physiology of algae (e.g. Einali et Shariati 2012, Zhou et al 2013) and cyanobacteria (e.g. Bueno et al 2004, Zhang et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to antioxidative activity, other PG biological characteristics have also been demonstrated, such as anticancer, antifungal, and antibacterial properties (kratz et al 2008). It is frequently used as a specific inhibitor of plastid terminal oxidase (PTOX) involved in chlororespiration, in photosynthetic investigations (Cournac et al 2000;Kuntz 2004;Gamboa et al 2009;Einali and Shariati 2012). Our recent study displayed that PG concentration of 1 mM leads to an increase in pigment content and improvement of the efficiency of photosystem II in D. salina (Einali and Shariati 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently used as a specific inhibitor of plastid terminal oxidase (PTOX) involved in chlororespiration, in photosynthetic investigations (Cournac et al 2000;Kuntz 2004;Gamboa et al 2009;Einali and Shariati 2012). Our recent study displayed that PG concentration of 1 mM leads to an increase in pigment content and improvement of the efficiency of photosystem II in D. salina (Einali and Shariati 2012). Other studies have shown that exogenous utilization of some antioxidants and signal molecules, such as ascorbate and salicylic acid, can induce the antioxidant systems and enhance plant resistance against abiotic stress (Li et al 1998;He et al 2002;Athar et al 2008;Saruhan et al 2012).…”
Section: Introductionmentioning
confidence: 99%